Digital platforms’ boundaries: The interplay of firm scope, platform sides, and digital interfaces - Gawer, Annabelle (Long range planning, 2021)
This article explores what factors drive digital platform firms to set or modify their boundaries. Building on economics, strategic management, and information systems research, I suggest that digital platforms make strategic decisions over three distinct types of interrelated boundaries: (1) the scope of the platform firm (what assets are owned, what labor is employed, and what activities are performed by the firm), (2) the configuration and composition of the platform's sides (which distinct groups of customers have access to the platform), and (3) the digital interfaces (that specify the 2-way exchange of data between the platform firm and each of its sides). In this article, I explore the interdependence between these seemingly separate decisions and the role of some important moderating variables. These moderators include whether the platform is a transaction or an innovation platform, and the extent to which the platform has developed from its initial formation stage. My work explains why we see so much variation in boundaries across platforms and over time.